EFFECT OF SUV BODY GEOMETRY ON AERODYNAMIC DRAG AND FUEL EFFICIENCY USING CFD - Arifin Oktobrian Winanta; Dewandono Bayu Seto; Onery Andi Saputra (Mechanical Engineering Department, Faculty of Engineering, Universitas Lambung Mangkurat, 2026)
The increasing demand for fuel efficiency in the automotive industry, particularly in the sport utility vehicle (SUV) segment, has intensified research on factors influencing vehicle energy efficiency. One of the most important factors is vehicle aerodynamic performance, especially air resistance characterized by the drag coefficient. This study analyzes the influence of SUV body shape variations on aerodynamic performance and fuel consumption using Computational Fluid Dynamics (CFD) simulations. Two SUV models with different body geometries, namely boxy and streamlined configurations, were analyzed under identical operating conditions to ensure a consistent comparison. The simulation results show that the streamlined model reduces the drag coefficient from 0.46 to 0.325, corresponding to an approximate 29% reduction compared to the boxy configuration. This aerodynamic improvement is associated with better fuel efficiency, particularly at higher vehicle speeds. At a speed of 120 km/h, the streamlined configuration achieves a fuel efficiency of 13.2 km/L, while the boxy configuration reaches only 9.03 km/L under the same conditions. These findings indicate that optimizing vehicle body geometry through aerodynamic design can significantly improve fuel efficiency and reduce aerodynamic resistance in SUV vehicles.